ALGORITHMS OF GRAPH THEORY AND OPTIMIZATION OF THE SPECIAL OBJECT HEATING - A. N. Chichko; A. V. Borozdin; O. A. Sachek (Литьë и металлургия)
Algorithm of the slug heating optimal regime at stepwise multizone heat supply is presented. The algorithm allows to optimize the heating regimes of slugs of arbitrary three-dimensional configuration on different criteria at given technological limits imposed on the slug heating process.